2019
DOI: 10.1016/j.drugalcdep.2018.11.029
|View full text |Cite
|
Sign up to set email alerts
|

Cluster randomized stepped-wedge trial of a multi-level HIV prevention intervention to decrease amphetamine-type stimulants and sexual risk in Cambodian female entertainment and sex workers

Abstract: CM developed the protocol for this cluster randomized stepped-wedge trial with comments and feedback from the entire study team. KP, AWS, ES, MS, PM and SN developed and implemented standard operating procedures for conducting assessments as well as delivering the multi-level CIPI intervention and ensuring protocol fidelity. AWC and CS adapted evidence-based CCT and cognitive-behavioural interventions targeting stimulant use with substantial contributions by Ean Nil (see acknowledgements). ES and KP developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Cash transfers are common instruments in LMICs. [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] Over the last 10 years, scientific publications have evaluated cash transfer programs in 31 countries. The studies looked at the…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Cash transfers are common instruments in LMICs. [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] Over the last 10 years, scientific publications have evaluated cash transfer programs in 31 countries. The studies looked at the…”
Section: Plos Onementioning
confidence: 99%
“…impact of cash transfers on maternal health, [29,30] maternal mental health, [31] neonatal and infant mortality, [32,33] childhood malnutrition, [34,35] childhood vaccinations, [36,37] childhood illness, [38] childhood and adolescent education, [39,40] sexual and reproductive health practices of sex workers, mothers and adolescents, [41,42] geriatric health, [43] HIV incidence [44] and prevalence of high risk behavior for HIV, [45] and incidence of TB. [46] Only one study evaluated the impact of cash transfers on the uptake of surgical services, specifically C-sections in Mexico.…”
Section: Plos Onementioning
confidence: 99%
“…In terms of evaluation research, the above-mentioned study was the only solid effort found in this scoping review. This is surprising if one considers that large scale randomised trials have been conducted to assess HIV intervention effectiveness among Cambodian entertainment and sex workers, for example [57].…”
Section: Discussionmentioning
confidence: 99%
“…For example, had the Cambodian CIPI trial proceeded to incentivize women to participate by offering US$1 for a urine screening visit, suboptimal recruitment leading to insufficient power to show an effect of the intervention may have resulted. Under‐incentivizing CIPI participants also had the potential to result in sampling bias with only impoverished women enrolling in the trial, compromising external validity and leading to non‐generalizable findings .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they expressed concerns about directly observed urine specimen collection and emphasized the need for enjoyable, as well as educational, content in the after‐care programme. Revisions to the protocol were subsequently made to optimize both the acceptability of the intervention and the implementation of the trial …”
Section: Qualitative Research and Rcts In Addiction Sciencementioning
confidence: 99%